SINTESIS DAN KARAKTERISASI SENYAWA KOMPLEKS TETRAMMINETEMBAGA(II) SULFAT [CU(NH3)4]SO4 - Fardaniah, Raziqah; Si’arif Hidayat Daeli; Ari Ramadana; Mustika Anjani Hutagaol, Sari; Siti Jahro, Iis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to synthesize and characterize the complex compound tetraamminecopper(II) sulfate [Cu(NH₃)₄]SO₄ based on coordination chemistry principles. The research was conducted using a laboratory experimental method with a simple experimental design. The synthesis was carried out by reacting copper(II) sulfate pentahydrate with concentrated ammonia, followed by the addition of ethanol to induce crystallization and cooling using an ice bath. The resulting crystals were filtered, washed, and dried before further characterization. Data were collected through direct observation of color changes, crystal formation, and solubility behavior, as well as mass measurement to determine the yield. The results showed that the synthesis produced dark blue crystals with a mass of 1.21 g and a yield of 53.1%. The formation of the complex was indicated by a color change from light blue to deep blue due to ligand substitution from water to ammonia. Solubility tests revealed that the compound was soluble in polar solvents (H₂O and NH₄OH) and insoluble in nonpolar solvents (CHCl₃ and ethanol), confirming its ionic and polar nature. These findings were consistent with coordination chemistry theory, indicating that the synthesized compound possessed the expected structural and physicochemical properties.